G345 Impact of a Neonatal Echocardiography clinic service in a Level 3 NICU centre. (7th April 2014) - Palanisami, B; Rakhecha, A; Gottstein, R
Abstract : Introduction: Asymptomatic cardiac murmurs are commonly detected on first day newborn examination. Majority of these get referred to cardiology services, as majority of the healthy term babies are discharged home on the first day of life. The waiting period for evaluation of the neonates by the Paediatric cardiology services is increasing partly because of increased identification of asymptotic murmur and increasing survival of children with critical and serious congenital heart disease. We recognised the increased waiting time for evaluation of the neonates with asymptomatic murmur and started Neonatal echocardiography clinic 2 years ago. Aim: To analyse the Neonatal echocardiography service in a Level 3 NICU over a 2 year period and assess it's impact on neonatal cardiology referral pattern. Methods: Retrospective analysis of case notes of all the infants who attended the Echocardiography clinic from January 2012 to October 2013. Results: A total of 56 neonatal echocardiography clinics were conducted during the period. 133 patients were seen on 152 occasions. Median gestational age, weeks (range) was 39 (28–42), Median age seen in the clinic, days (range) was 41 (2 – 202). Junior doctors interested in learning echocardiography attended 24 clinics. Cardiac pathologies were identified in 39% (52/133). Conclusion: This model has worked effectively in discharging nearly half of the referrals which do not need cardiology input thus decreasing the burden on the cardiologist. These babies were seen earlier than would have been seen in the cardiology clinic and unwanted parental anxiety was avoided. The clinic also helps junior doctors particularly in Neonatal higher speciality training to develop their Echocardiography skills under supervision.